If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(9x + 9) + 6 = 0 Reorder the terms: -8(9 + 9x) + 6 = 0 (9 * -8 + 9x * -8) + 6 = 0 (-72 + -72x) + 6 = 0 Reorder the terms: -72 + 6 + -72x = 0 Combine like terms: -72 + 6 = -66 -66 + -72x = 0 Solving -66 + -72x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '66' to each side of the equation. -66 + 66 + -72x = 0 + 66 Combine like terms: -66 + 66 = 0 0 + -72x = 0 + 66 -72x = 0 + 66 Combine like terms: 0 + 66 = 66 -72x = 66 Divide each side by '-72'. x = -0.9166666667 Simplifying x = -0.9166666667
| 15-(4v+4)=-4v-11 | | 5x+x+60=90 | | 6+(3+b)= | | 4(4-2x)=24-4x | | 5x+2y+2=80 | | 2*2-18x=0 | | 5+2n-3n=8 | | A=zm+zform | | -8x-62=64-2x | | x+3x-2=78 | | 128=96t-16t^2 | | 4y+8=4y-9 | | -8=9v-5+32 | | s-3=5-2 | | 10=5(x+3) | | 3x+18=x+32 | | 5w+8-w=7w-2(w-4) | | 1-3=5-1 | | 7m-3=9m+6-m | | -85+3x=83-9x | | (5x-3)+(n+9)=24 | | X^3+13x^2=0 | | 6y+4=6y-9 | | 16(z+3)=4(z-9) | | (2x-4)(x+3)= | | 2a-4b=58 | | -a+5=5a+5 | | 3x-7=-3 | | F(5)=20x+11 | | 4x^3+8x^2+3x+6=0 | | q-rb=15a | | 2x+12i=3y+2yi |